Postmodern Culture - Foster Hal (Pluto Press, 1993)
This book should be read by anyone concerned with the practice and theory of contemporary art - Art in America. Postmodernism: A Preface, Modernity - An Incomplete Object, Towards a Critical Regionalism: Six Points for an Architecture of Resistance, Sculpture in the Expanded Field, On the Museum's Ruins, The Discourse of Others: Feminists and Postmodernism, The Object of Post-Criticism, Postmodernism and Consumer Society, The Ecstasy of Communication, Opponents and Audiences and Constituencies and Community.